Risk Mitigation of Oyster Mushroom Production and Distribution Using Method Failure Mode and Effect Analysis (FMEA) - Himmatul Miftah; Siti Rapigah; Syaima Lailatul Mubarokah; Siti Masithoh; Riny Kusumawati; Ikhsan Qodri Pramartaa (Indonesian Journal of Applied Research (IJAR), 2025)
The production process of making raw materials for horticultural commodities has various risks, both internal and external, and if it occurs, it will hinder the company's goals. This research aims to analyse and measure risks in the production and distribution of oyster mushrooms and determine actions to mitigate risks. The research method used purposive and snowball sampling. Data were analysed using descriptive analysis through interviews and quantitatively through risk analysis and Failure Mode and Effect Analysis (FMEA) methods. The study results indicated that risks occur from the nursery stage to distribution to consumers. Risk mapping that needs to be watched out for: Mucor spp disease, baglogs attacked by crepe pests, damaged baglogs in the incubation section, and incorrect and irregular watering and fertilization. The risks in distribution analysed are the risk of heavy losses, physical damage, and unsold goods. The most significant risks in the distribution process were heavy losses and physical damage to mushrooms at the farmer level during the sorting process, and physical damage at the retailer level during the sorting process due to the presence of old, wet, and yellowing mushrooms, as well as unsold mushrooms. Production is mitigated by cleaning around the mushroom house, burning diseased baglogs, arranging baglog entry and exit times to facilitate the sorting process, and implementing routine work direction and evaluation. Mitigation of unsold risks during distribution: making a purchasing plan according to previous sales results, selling remaining mushrooms at a lower price than the purchase price, and using PBP and VBP packaging.